2012
DOI: 10.1091/mbc.e12-02-0142
|View full text |Cite
|
Sign up to set email alerts
|

Physical association of the WC-1 photoreceptor and the histone acetyltransferase NGF-1 is required for blue light signal transduction in Neurospora crassa

Abstract: Neurospora and higher eukaryotes share a common mechanism for the signal transduction of environmental stimuli. A scenario is given in which the Neurospora WC-1 photoreceptor represents a function orthologous to that of vertebrate nuclear receptors, acting through the association with the HAT NGF-1 via a vertebrate-like LXXLL motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 40 publications
4
46
0
Order By: Relevance
“…This suggests that the WCC recruited to the PLRE in the light recruits functional coactivators other than SWI/SNF to modify the PLRE in frq transcription. Additionally and consistent with this, the PLRE is located adjacent to the TSS site and WCC acts on these regions neither by looping of the DNA to bring activators to the TSS, nor by wholesale remodeling of chromatin, although epigenetic modifications have been noted [32], [39], [59]. This suggests that major remodeling and looping induced by SWI/SNF are principal factors distinguishing circadian activators at the C box versus light activators at the PLRE .…”
Section: Discussionmentioning
confidence: 57%
“…This suggests that the WCC recruited to the PLRE in the light recruits functional coactivators other than SWI/SNF to modify the PLRE in frq transcription. Additionally and consistent with this, the PLRE is located adjacent to the TSS site and WCC acts on these regions neither by looping of the DNA to bring activators to the TSS, nor by wholesale remodeling of chromatin, although epigenetic modifications have been noted [32], [39], [59]. This suggests that major remodeling and looping induced by SWI/SNF are principal factors distinguishing circadian activators at the C box versus light activators at the PLRE .…”
Section: Discussionmentioning
confidence: 57%
“…This acetylation is carried out by histone acetyltransferase (HAT) NGF-1, and NGF-1 directly interacts with WC-1. Given that NGF-1 was found to interact with “dark” WC-1/2 heterodimer, a model has been proposed wherein light activation of the WCC/NGF-1 complex leads to conformational changes in WCC (converting it to “light” WCC) which in turn leads to an enhancement of HAT activity of NGF-1 (Brenna et al , 2012). More recently, H3K9me3 DNA methylation by methyltransferase DIM-5 and HP1 has been identified to be a component in the repression of light-induced gene expression (Ruesch et al , 2014), and there is higher light-induced transcription of two genes, frq and vvd , in a dim-5 mutant.…”
Section: N Crassa: a Model Organism For Studying Photobiologymentioning
confidence: 99%
“…T. atroviride contains the classical HDAC classes I, II, and III (28). A connection between light responses and histone acetylation in filamentous fungi has been demonstrated in N. crassa, in which both WC-1 and NGF-1 (orthologous to Gcn5p) physically interact to promote light-induced acetylation of residue K14 of histone H3 associated with the promoter of the al-3 gene (29,30). Recently, it was demonstrated that light activation of WC-1 and -2 is related to nucleosome removal at their target promoters.…”
mentioning
confidence: 99%